Lęk ironistki. Jażń ludzka w kulturze literackiej Richarda Rorty'ego - Pietrzak, Wit (Er(r)go. Teoria - Literatura - Kultura, 2014)
The Ironist’s Fear. The Human Self in Richard Rorty’s Literary Culture. Build on the anti-essentialist foundations that were raised by Nietzsche and Derrida, Richard Rorty’s post-metaphysical vision of literary culture entails two crucial concepts: irony and solidarity. The present article intends to highlight the presence of a third, less perceptible key idea: fear. The ironist’s description(s) of the world, involve(s) ever-changing vocabularies, adaptable according to the demands of new situations and emerging different forms of otherness, vocabularies which are shaped and reshaped by encounters with the ever-extending line of literary works, with the awareness of the inability to find or settle for the “final vocabulary.” It is precisely this awareness, which may, under certain circumstances, be seen as evoking a possibility of fear that concerns not only the stability of one’s identity, but also the inability of a complete and satisfactory expression. This fear, however, does not necessarily has to have a stunting effect – it may be responsible for the stimulation of one of man’s most powerful qualities: creativity.